2012
DOI: 10.1111/sode.12007
|View full text |Cite
|
Sign up to set email alerts
|

Social Competence in Preschool Children: Replication of Results and Clarification of a Hierarchical Measurement Model

Abstract: This study tested assumptions and conclusions reached in an earlier

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
21
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 36 publications
9
21
0
3
Order By: Relevance
“…Social competence and social preference were positively associated with one another, confirming previous findings (Bost et al, 1998;Cillessen, Schwartz, & Mayeux, 2011;Santos et al, 2013). In this study social competence was conceptualized as the overall ability to develop positive interactions with others and to achieve one's own goals without hurting others (Vaughn et al, 2009;Waters & Sroufe, 1983).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Social competence and social preference were positively associated with one another, confirming previous findings (Bost et al, 1998;Cillessen, Schwartz, & Mayeux, 2011;Santos et al, 2013). In this study social competence was conceptualized as the overall ability to develop positive interactions with others and to achieve one's own goals without hurting others (Vaughn et al, 2009;Waters & Sroufe, 1983).…”
Section: Discussionsupporting
confidence: 84%
“…A total of five trained observers separately conducted about 20 hr of observation in the classroom during 1 week, completing at least 1 hr and a half of observations per each child. One hundred sixty-one children (50.3% of the total sample) were observed by two trained observers: Cross-rater agreement on criterion scores was satisfactory (r ¼ .70, for the CCQ, and r ¼ .60, for the PQ) and in line with those reported elsewhere (Santos et al, 2013;Vaughn et al, 2009). The score assigned to each item is its placement in the distribution.…”
Section: Methodssupporting
confidence: 57%
“…These results are also in line with research using other methods. Two previous cross-cultural studies using different assessment methods have reported comparable gender differences in social competence, namely girls had higher peer sociometric acceptance (Santos, Peceguina, Daniel, Shin, & Vaughn, 2013;Santos, Vaughn, Peceguina, Daniel, & Shin, 2014). As to gender differences in anger-aggression, Ostrov and Keating (2004) found that preschool boys displayed more physical and verbal aggression than girls, while girls displayed more relational aggression than boys.…”
Section: Sex Differencesmentioning
confidence: 96%
“…This code configuration captures a target child's affect expression during an interaction with another child while engaged in a specific activity; the observation occurs during a 15 s window of time [10][11]. With this interface, the observer codes the initiator and target of the interaction plus the observed affective valence (positive, neutral and negative).…”
Section: Affect Expressionmentioning
confidence: 99%
“…One variation of pyObs was the foundation coding system used to capture visual attention among preschoolers [10][11]. To gather these data, observers watched a target child for a 6 s interval and recorded the identity of peers receiving a unit of visual regard, along with affect, from the target; visual regard, defined as the orientation of head and eyes toward the peer recipient, measures social engagement.…”
Section: Visual Attentionmentioning
confidence: 99%